Root and tuber crops in St. Vincent - Browne, G.E. (International Center for Tropical Agriculture, 1986)
The var. of Colocasia esculenta var. antiquorum, taro, cocoyam, sweet potato, and yam cultivated in St. Vincent are described in detail, and the availability of land and potential expansion, farm characteristics, cropping systems, internal and external demand, and market systems are indicated. A comprehensive study on production costs of these crops is also presented. Cassava is grown in the regions of Dorsetshire Hill and Argyle, but its production is insignificant. It is sown in mixed cropping systems (sweet potato/maize/cassava, sweet potato/cowpea/cassava, sweet potato/cowpea/maize/cassava). Cassava is the only root crop processed; farine is the main by-product, produced in home-based industries. Arrowroot starch production has slowly replaced cassava starch production. Finally, production constraints and the future direction of research are discussed. (CIAT)